2020
DOI: 10.1371/journal.pone.0233124
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis timing may be deferred toward very late initiation: An observational study

Abstract: The optimal timing to initiate dialysis among patients with an estimated glomerular filtration rate (eGFR) of <5 mL/min/1.73 m 2 is unknown. We hypothesized that dialysis initiation time can be deferred in this population even with high uremic burden. A case-crossover study with case (0-30 days before dialysis initiation [DI]) and control (90-120 days before DI) periods was conducted in 1,079 hemodialysis patients aged 18-90 years at China Medical University Hospital between 2006 and 2015. The uremic burden wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
(45 reference statements)
0
10
0
1
Order By: Relevance
“…Hence, a number of other studies paid attention to comprehensive assessment of uremic signs and/or symptoms for optimal dialysis initiation. Chang et al [17] quanti ed uremic burden based on 7 uremic indicators that reached the prede ned threshold (hemoglobin, serum albumin, blood urea nitrogen, serum creatinine, potassium, phosphorus, and bicarbonate); dialysis timing was classi ed as standard (met 0-2 uremic indicators), late (3-5indicators), and very late (6-7 indicators); and no correlation was found between late or very late group and mortality. Ying et al [26] developed an equation based on fuzzy mathematics to assess the timing of haemodialysis initiation, the results showed that the combination of sex, age, serum creatinine, blood urea nitrogen, serum albumin, haemoglobin, serum phosphorus, diabetes mellitus, and heart failure as equation variables resulted in the best accuracy to prognose 3-year survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, a number of other studies paid attention to comprehensive assessment of uremic signs and/or symptoms for optimal dialysis initiation. Chang et al [17] quanti ed uremic burden based on 7 uremic indicators that reached the prede ned threshold (hemoglobin, serum albumin, blood urea nitrogen, serum creatinine, potassium, phosphorus, and bicarbonate); dialysis timing was classi ed as standard (met 0-2 uremic indicators), late (3-5indicators), and very late (6-7 indicators); and no correlation was found between late or very late group and mortality. Ying et al [26] developed an equation based on fuzzy mathematics to assess the timing of haemodialysis initiation, the results showed that the combination of sex, age, serum creatinine, blood urea nitrogen, serum albumin, haemoglobin, serum phosphorus, diabetes mellitus, and heart failure as equation variables resulted in the best accuracy to prognose 3-year survival.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [14] demonstrated that after adjusting for effectors of age, gender, diabetes, type of vascular access at initiation, clinical signs, and/or symptoms at the initiation of dialysis, and serum albumin, there was no signi cant difference in survival rate between the 3 groups (< 4 mL/min/1.73 m 2 was used as the reference, in comparison with 4-8 mL/min/1.73 m 2 [p = 0.681] and > 8 mL/min/1.73 m 2 [p = 0.403]). Chang et al [17] also found the fully adjusted hazards ratios of mortality for the late (3-5indicators) and very late (6-7 indicators) groups were 0.97 (95% con dence interval 0.76-1.24) and 0.83 (0.61-1.15) compared with the standard (met 0-2 uremic indicators) group. The 7 uremic indicators that reached the prede ned threshold in case period, namely hemoglobin, serum albumin, blood urea nitrogen, serum creatinine, potassium, phosphorus, and bicarbonate.…”
Section: Study Outcomesmentioning
confidence: 90%
See 1 more Smart Citation
“…All patients enrolled in the CMUH-CRDR were followed up until December 31, 2017, or death—whichever occurred earlier. The description of CMUH-CRDR had been reported in our previous work 31 , 32 .…”
Section: Methodsmentioning
confidence: 99%
“…La progresión de las alteraciones bioquímicas del metabolismo mineral en pacientes con ERC avanzada en prediálisis se acompaña de una pérdida de la función renal residual. Las medidas dietéticas de restricción de fosfato en la dieta en pacientes en prediálisis tienen el riesgo de desnutrición energético-proteica 54 y un inicio tardío de la diálisis 55 , por lo cual los autores consideran que los individuos con síntomas urémicos vinculados con elevación progresiva de la PTHi o hiperfosfatemia deben valorarse para el inicio del tratamiento de sustitución de la función renal 56 .…”
Section: A39 Se Recomienda Que Los Pacientes Con Erc G5d Pthi Elevada Y Cifras Normales De Calcemia Y Fosfatemia Reciban Como Tratamientounclassified